Question:
1) Blue triangle points; (-1, 4), (-5, 4), and (-1, 1)
Red triangle points; (-4, -1), (-1, -1). and (-4, -5)
2) Blue triangle points (1, 1), (4, 5), (4, 1)
Red triangle points; (-1, 1), (-1, 4). and (-5, 4)
3) Blue triangle points (0, 1), (4, 4), (4, 1)
Red triangle points; (-4, 1), (-4, 4). and (0, 1)
4) Blue triangle points (-5, 4), (-1, 4), (-1, 1)
Red triangle points; (1, 1), (4, 1). and (4, 5)
5) Blue triangle points (-2, 5), (4, 5), (4, 1)
Red triangle points; (-1, 4), (-5, 4). and (-5, -2)
Answer:
The correctly rotated red triangles are those of (1), (2), and (5)
Step-by-step explanation:
In a 90° counterclockwise rotation, every x and y points of the original triangle are switched while the y is turned negative, as shown in the following equation;
(x, y) to (-y, x)
Therefore, the triangles that undergo a 90° counterclockwise rotation are as follows;
1) Blue triangle points; (-1, 4), (-5, 4), and (-1, 1)
Red triangle points; (-4, -1), (-1, -1). and (-4, -5)
(-1, 4) → (-4, -1)
(-5, 4) → (-4, -5)
(-1, 1) → (-1, -1)
Correctly rotated 90° counterclockwise
2) Blue triangle points (1, 1), (4, 5), (4, 1)
Red triangle points; (-1, 1), (-1, 4). and (-5, 4)
(1, 1) → (-1, 1)
(4, 5) → (-5, 4)
(4, 1) → (-1, 4)
Correctly rotated 90° counterclockwise
3) Blue triangle points (0, 1), (4, 4), (4, 1)
Red triangle points; (-4, 1), (-4, 4). and (0, 1)
(0, 1) → (0, 1) ≠ (-1, 0)
(4, 4) → (-4, 4)
(4, 1) → (-4, 1)
Not correctly rotated 90° counterclockwise
4) Blue triangle points (-5, 4), (-1, 4), (-1, 1)
Red triangle points; (1, 1), (4, 1). and (4, 5)
(-5, 4) → (4, 5) ≠ (-4, -5)
(-1, 4) → (4, 1)
(-1, 1) → (1, 1)
Not correctly rotated 90° counterclockwise
5) Blue triangle points (-2, 5), (4, 5), (4, 1)
Red triangle points; (-1, 4), (-5, 4). and (-5, -2)
(-2, 5) → (-5, -2)
(4, 5) → (-5, 4)
(4, 1) → (-1, 4)
Correctly rotated 90° counterclockwise.
Answer:
1,2,5
Step-by-step explanation:
on average, how many times must a 6-sided die be rolled until the sequence 65 appears (i.e., a 6 followed by a 5)?
A 6-sided die must be rolled 36 times before sequence 65 appears. (i.e., a 6 followed by a 5)
What is probability?Probability is defined as the possibility of an event being equal to the ratio of the number of favorable outcomes and the total number of outcomes.
Let E as the expected rolls, and E₆ as the expected rolls given we rolled a 6.
Given that we rolled a 6, there is a 1/6 chance that two rolls will be enough, a 4/6 chance that we didn't roll a 5 or 6 and so spent two rolls, and a 1/6 chance that we rolled a 6 and only wasted one roll:
E₆ = (1/6)2 + (4/6)(E+2) + (1/6)(E₆ + 1)
Rearrange the terms and apply arithmetics operations
E₆ = (4E + 11)/5
According to the question,
We have 5/6 that we rolled [1,5]
So we wasted a roll, and 1/6 that we rolled a 6,
E = (1/6)×E₆ + (5/6)×(E+1)
Substitute the value of E₆ in the equation,
E = (1/30)×(4E+11) + (5/6)×(E+1)
E = 36
Hence, a 6-sided die must be rolled 36 times before sequence 65 appears.
Learn more about probability here:
brainly.com/question/11234923
#SPJ4
what number is the opposite of 0.93?
Answer:
- 0.93
Step-by-step explanation:
0.93 has an absolute value of 0.93 and is positive, so its opposite would be negative with the same absolute value.
The opposite number of 0.93 is -0.93.
What is opposite number?The number that produces zero when added to an is known as the additive inverse of a number, or a, in mathematics. This number is also referred to as the opposite number. In another word, oppositely positioned numbers on the number line are called opposite number.
Hence, opposite number of a positive number is a negative number and opposite number of the negative number is a positive number.
For an example, the opposite number of +7 is -7 because +7 + ( -7) = 0.
The opposite number of -0.5 is 0.5 because (-0.5) +0.5 = 0.
In this question, the given number is +0.93.
Let the opposite number of +0.93 is x.
Then it can be written that:
+0.93 + x = 0
⇒ x = 0 -0.93
⇒ x = -0.93
Hence, the opposite number of 0.93 is -0.93.
Learn more about opposite numbers here:
https://brainly.com/question/28492868
#SPJ3
dr. martinez conducted a survey to determine the frequency of sexual activity among the american middle class. he collected data from several individuals working at various multinational companies and concluded that an average middle-class american engages in sexual activity once in a week. in this scenario, dr. martinez's research sample is most likely a
If Dr.Martinez conducted a survey to determine the frequency of sexual activity among the American middle class and collected data from several individuals working at various multinational companies then the research sample is most likely a Convenience Sample .
A Convenience Sample is defined as a type of non-probability sampling method where the researcher selects the sample based on ease of access or availability.
In this survey , Dr. Martinez collected data from individuals who were readily available to him, such as people he knew working at various multinational companies, rather than using a method that would allow him to randomly select a representative sample of the middle class.
The results of this study cannot be generalized to the entire middle class population, as the sample may not be representative of the population.
Therefore , the the research sample is a Convenience Sample .
Learn more about Convenience Sample here
https://brainly.com/question/1413932
#SPJ4
How do I simplify (7w)2
Answer:
14w
Step-by-step explanation:
You just need to multiply what's inside by 2.
HELP ME
solve x^4-17x^2+16=0
select all of the solutions to the original equation
x=4
x=-16
x=-4
x=16
x=-8
x=-1
x=1
x=8
The mathematical equation relating the expected value of the dependent variable to the value of the independent variables, which has the form of E(y) = β0 + β1x1 + β2x2 + β3x3 +...+ βpxp is:
a. a multiple regression equation. b. a simple linear regression model. c. a multiple nonlinear regression model. d. an estimated multiple regression equation.
The mathematical equation relating the expected value of the dependent variable to the value of the independent variables, which has the form of E(y) = β0 + β1x1 + β2x2 + β3x3 +...+ βpxp is a multiple regression equation. The correct option is (a).
The equation E(y) = β0 + β1x1 + β2x2 + β3x3 +...+ βpxp represents a multiple regression equation. Multiple regression analysis is a statistical method used to examine the relationship between a dependent variable and multiple independent variables.
In this equation, E(y) represents the expected value of the dependent variable, which is a function of multiple independent variables, x1, x2, x3, ...xp.
The β0, β1, β2, β3,...βp are the regression coefficients, which represent the expected change in the dependent variable for each unit change in the corresponding independent variable, while holding all other independent variables constant.
The multiple regression equation is used to model the relationship between the dependent variable and the independent variables, taking into account the possible effect of each independent variable on the dependent variable while controlling for the effect of other independent variables.
This makes it a useful tool for predicting the values of the dependent variable based on the values of the independent variables.
In contrast, a simple linear regression model only involves one independent variable, and a multiple nonlinear regression model involves nonlinear relationships between the dependent variable and multiple independent variables.
An estimated multiple regression equation is simply a fitted equation based on the sample data, which can be used to make predictions or inferences about the population.
Therefore, the correct answer is option (a) a multiple regression equation.
To know more about multiple regression equation refer here:
https://brainly.com/question/30063703#
#SPJ11
Your mom Paid $8 for 10 Granny Smithapples and bought 15 Golden Delicious at60 cents an apple. What is her average costper apple?
First, let's find the total cost of all the apples:
\(8+(0.6\cdot15)=17\)Now, we divide this by the total amount of apples bought. In our case, we know that there were 10 Granny Smith apples and 15 Golden Delicious, for a total of 25 apples.
\(\frac{17}{25}\rightarrow0.68\)Therfore, we can conclude that the average cost per apple was $0.68
Which equation represents a line which is parallel to y=0?
A x=1
B y=x
C y= x+3
D y=6
Any line whose equation is in the form y = k shall be parallel to the line of y = 0.
Answer:
\(D \: y=6\)
Step-by-step explanation:
SORRY IF THIS IS WRONG......
(144\(k{2}\)\(r{2}\))\(1/2\)
Answer:
Step-by-step explanation:
7hs
Yes
NEED HELP ASAP!!!
Review the diagram.
On a coordinate plane, a vector labeled 120 meters forms angle 25 degrees with the x-axis. It goes to point mirror 1. Another vector labeled 90 meters goes from point mirror 1 to mirror 2. It forms angle 20 degrees with a horizontal line. Point mirror 2 goes to (0, 0).
A laser beam is aimed 25° from horizontal at a mirror 120 m away. The beam bounces off the mirror and continues for an additional 90 m at 20° above horizontal until it hits a target, mirror 2. What is the distance between the origination point and the target?
approximately 85 m
approximately 122 m
approximately 174 m
approximately 194 m
Answer:
Approximately 85 m
Step-by-step explanation:
Let x represent the distance between the origination point and the target
Distance between original point and mirror 1 = 120 m
Distance between mirror 1 and mirror 2 = 90 m
The measure of angle Opposite the distance between the origination point and the target = 20 + 25 = 45°
Use Cosine rule to find x as shown below:
Use The Law of Cosines to find side a first:
\( a^2 = b^2 + c^2 - 2bc \times Cos(A) \)
Where,
a = x
b = 90 m
c = 120 m
A = 45°
Plug in the values
\( x^2 = 90^2 + 120^2 - 2(90)(120) \times Cos(45) \)
\( x^2 = 22,500 - 21,600 \times Cos(45) \)
\( x^2 = 22,500 - 15,273.5065 \)
\( x^2 = 7,226.4935 \)
Square both sides
\( x = \sqrt{7,226.4935} \)
\( x = \sqrt{7,226.4935} \)
x ≈ 85 m
Answer: AAAAAAA-85!!!!!
Step-by-step explanation:
the conditions that the sum of forces and the sum of the torques both vanish:
Answer and Explanation: The conditions when the net force and the net torque are zero are called static equilibrium.
The lengths of two sides of a triangle are 4 inches and 7 inches. What is a possible length, in inches, of the third side?
Answer:
well if im wrong then sorry but i think its 11 !!
Step-by-step explanation:
The possible length of the third side should be greater than 11.
What is triangle?A triangle is a polygon with three sides having three vertices. The angle formed inside the triangle is equal to 180 degrees. It means that the sum of the interior angles of a triangle is equal to 180°.
Given that the lengths of two sides of a triangle are 4 inches and 7 inches.
We need to find the possible length of the third side,
So, according to the triangle inequality theorem,
For any given triangle, the sum of two sides of a triangle is always greater than the third side.
So, the sum of two sides = 4 + 7 = 11
Hence the possible length of the third side should be greater than 11.
Learn more about triangles click;
https://brainly.com/question/2773823
#SPJ2
Determine if the given function is continuous at a given value of x. Show the solution.
This question is taken from the continuity and discontinuity in which we have to check whether a given function is continuous at the given point or not continuous, so we can write the given function below
\(f(x)=\frac{3x}{x^2-4}\)at x=4 is continuous or not.
First, we are written the given function and check whether it is continuous at a given point or not, so we have to check the left hand and right-hand limit (LHL and RHL)are equal or not, Given a function
\(f(x)=\frac{3x}{x^2-4}\)so formula we write it below at the given point
LHL=limx→−4−k(x)
RHL=limx→−4+k(x)
and applicable only limits are exist otherwise discontinuous.
RHL=LHL=k(4)
if the above formula is satisfy then the given function is continuous
now we calculate the L.H.L
LHL=limx→−4−k(x)
\(\text{LHL}=\lim _{x\rightarrow-4^-}\frac{3x}{x^2-4}\)Now change the limit, x=-4-h and h=0.
\(LHL=\lim _{h\rightarrow0}\frac{3(-4-h)}{(-4-h)^2-4}=\frac{-12}{12}=-1\)For RHL,
\(\text{RHL}=\lim _{h\rightarrow0}\frac{3(4-h)}{(4-h)^2-4}=\frac{12}{12}=1\)For x=4,
\(f(4)=\frac{3\times4}{4^2-4}=\frac{12}{12}=1\)So RHL is not equal to LHL but RHL = for the function at x=4.
Then it is not satisfied the continuous property so the function is discontinuous at x=4.
So its function value is discontinuous at x= 4.
if f(x)=-2x-3 what is f(r+2) ?
Answer:
\(f(x) = - 2x - 3\)
when x is r + 2 :
\(f(r + 2) = - 2(r + 2) - 3 \\ = - 2r - 4 - 3 \\ = - 2r - 7 \\ \\ { \boxed{ \boxed{f(r + 2) = - 2r - 7}}}\)
Can the sides of a triangle have lengths 1, 4, and 7?
Answer:
No
Step-by-step explanation:
No because the measure of two sides are always greater than the third side
Subscribe my Gaming channel Sameer Duos
The ratio of 1.4 to 26 is the same as the ratio of 2.8 to ____.
Britney invested $500 in stocks. After one year, the value of her stocks has increased to $530. Britney wants to use the growth from the first year to estimate future growth. Write an exponential equation in the form y=a(b)x that can model the estimated value of Britney's stocks, y, after x years. Use whole numbers, decimals, or simplified fractions for the values of a and b.
Answer:gy
Step-by-step explanation:yg
A triangle has sides with lengths of 10, 15, and 6 feet. Find the perimeter of a similar triangle whose shortest side is 7
Answer:
P = 36 1/6 feet
Step-by-step explanation:
you can create the following proportion:
6 / 7 = 10 / x
cross-multiply:
6x = 70
x = 11 2/3
use the same ratio to write a second proportion to find the last side:
6 / 7 = 15 / x
cross-multiply:
6x = 105
x = 17 1/2
Perimeter = 7 + 11 2/3 + 17 1/2 = 28 7/6 + 7 = 29 1/6 + 7 = 36 1/6 feet
The arclength of the curve F(t) = 2t+t2j+ (Int) k for 1
B. 35 3
C. 4+ In 2
D. 3+ In 2
E. 5+ In 2
Answer: The arclength of the curve is approximately 5.664 + ln(2), which is closest to option E (5+In 2).
Step-by-step explanation:
To get the arclength of the curve, we need to integrate the magnitude of its derivative over the interval of interest.
In this case, the curve is given by: F(t) = (t^2)i + (2t + ln(t))j + (ln(t))k.
So, the derivative of F(t) with respect to t is: F'(t) = 2ti + (2 + 1/t)j + (1/t)k and the magnitude of F'(t) is:|
F'(t)| = sqrt((2t)^2 + (2 + 1/t)^2 + (1/t)^2) = sqrt(4t^2 + 4t + 1/t^2 + 4/t + 1).
To get the arclength of the curve from t=1 to t=e^2, we need to integrate |F'(t)| over this interval: integral from 1 to e^2 of |F'(t)| dt = integral from 1 to e^2 of sqrt(4t^2 + 4t + 1/t^2 + 4/t + 1) dt.
This integral is difficult to evaluate analytically, so we can use numerical methods to approximate the value. Using a numerical integration tool, we get:integral from 1 to e^2 of |F'(t)| dt ≈ 5.664.
Therefore, the arclength of the curve is approximately 5.664 + ln(2), which is closest to option E (5+In 2).
Learn more about arclength here, https://brainly.com/question/2005046
#SPJ11
Pls help me on this someone pls
Answer: 9/10
=======================================================
Explanation:
Imagine a pizza split into 5 equal slices. Then imagine that you split each slice in half. This means we now have 5*2 = 10 slices.
Eating 3 out of the original 5 is equivalent to eating 6 smaller slices out of the now 10 total.
In other words: The fraction 3/5 is the same as 6/10
Put another way: Multiply top and bottom of 3/5 by 2 to get 6/10.
---------------
Gary painted 3/10 of the fence in the morning, and then 3/5 of it in the afternoon. We can replace the "3/5" with "6/10".
3/10 in the morning6/10 in the afternoon3/10 + 6/10 = (3+6)/10 = 9/10 total
Going back to the pizza scenario, we can imagine 3/10 as eating 3 slices out of 10 total. Then 6/10 adds 6 more slices to get 3+6 = 9 slices total. That's how we end up with 9/10 as the answer.
The volume of the Great Pyramid in Egypt is approximately 33,764 cubic meters. What is the volume, to the nearest tenth, of a scale model that is smaller by a scale factor of 1/12 ? need help with this question
Check the picture below.
\(\cfrac{1^3}{12^3}~~ = ~~\cfrac{V}{33764}\implies \cfrac{1}{1728}~~ = ~~\cfrac{V}{33764}\implies \cfrac{(1)(33764)}{1728}=V\implies \boxed{\stackrel{ cm^3 }{19.54}\approx V}\)
Write a numerical expression for the verbal expression. the sum of two an four and six times eight
The mathematical expression for the verbal expression is the sum of two and four and six times eight will be (2+4+6)8.
What is an expression?Expression in maths is defined as the collection of numbers variables and functions by using signs like addition, subtraction, multiplication, and division.
Numbers (constants), variables, operations, functions, brackets, punctuation, and grouping can all be represented by mathematical symbols, which can also be used to indicate the logical syntax's order of operations and other features.
Given verbal expression is the sum of two and four and six times eight will be written as:-
Add 2,4, and 6 apply parenthesis, and then multiply by 8. The expression will be:-
E = ( 2 + 4 + 6 ) 8
Therefore, the mathematical expression for the verbal expression is the sum of two and four, and six times eight will be (2+4+6)8.
To know more about an expression follow
https://brainly.com/question/2164351
#SPJ2
in the adjoining figure, ABC is a right-angled triangle, where
B = 90°, AB = 3 cm and AC
3V2 cm, find the size of ®.
Answer:
the value of theta i 45°
3 / 4/9 help pleasee
Answer:
3/4 divided by 9 (break it down) = 1/12
WILL GIVE BRAINLIEST NO LINKS ANSWER ASAP
a taste test asks people from Texas and California which pasta they prefer brand a or brand b this table shows the results a person is randomly selected from those tested what is the probability that the person is from Texas given that the person prefers brand a
0.62
0.47
0.45
0.64
Answer: 0.47
Step-by-step explanation: i just took the quiz
Sandra, Greg, and Michael team up for a competitive eating contest. If Sandra can eat 3 hot dogs per minute, Greg can eat 4 hot dogs per minute, and Michael can get 5 1/2 hot dogs per minute , how long will it take them to eat a combined total of 100 hot dogs?
It will take them 8 minutes to eat a combined total of 100 hot dogs.
Given,
Rate of eating hot dogs by sandra= 3/min
Rate of eating hotdogs by greg=4/min
Rate of eating hotdogs by michael =\(5\frac{1}{2}\) /min
To find the time taken by them together to eat 100 hot dogs can be calculated by
\(Time=\frac{Total\ hot\ dogs}{Sum\ of\ there\ rate\ of\ eating}\)
Sum of their rate of eating,
=\(=3+4+5\frac{1}{2}\\\\=7+\frac{11}{2}\\\\=\frac{14+11}{2}\\\\=\frac{25}{2}\)
Now,
\(Time=\frac{100}{\frac{25}{2}}=\frac{100*2}{25}=8 minutes\)
Thus, it will take them 8 minutes to eat a combined total of 100 hot dogs.
To learn more about work and time refer here
https://brainly.com/question/21220429
#SPJ1
How to find Y intercept of the line passing through the points
Answer:
Y-intercept: (0, -3)
Step-by-step explanation:
Given the two points, (6, 5) and (3, 1):
We can find the y-intercept by using the slope-intercept form, y = mx + b. However, the first step that we must do is to solve for the slope.
SlopeWe must first solve for the slope of the line using the following formula:
\(\displaystyle\mathsf{Slope\:(m) =\:\frac{y_2 - y_1}{x_2 - x_1}}\)
Let (x₁, y₁) = (3, 1)
(x₂, y₂) = (6, 5)
\(\displaystyle\mathsf{Slope\:(m) =\:\frac{y_2 - y_1}{x_2 - x_1}}\)
\(\displaystyle\mathsf{Slope\:(m) =\:\frac{5 - 1}{6 - 3}\:=\:\frac{4}{3}}\)
Hence, the slope of the line is: \(\sf{m\:=\frac{4}{3}}\) .
Y-intercept:Next, we must determine the y-intercept, which is the point on the graph where it crosses the y-axis, with coordinates of (0, b ).
In order to find the y-intercept, use one of the given points, (6, 5), and the slope, \(\sf{m\:=\frac{4}{3}}\), and substitute these values into the slope-intercept form and solve for the value of b:
y = mx + b
\(\displaystyle\mathsf{5\:=\:\frac{4}{3}(6)\:+\:b }\)
5 = 8 + b
Subtract 8 from both sides to isolate b:
5 - 8 = 8 - 8 + b
-3 = b
Therefore, the y-intercept is (0, -3), where b = -3.
of undetermined coefficients to solve (a) y' – 4y = 16xe -2x + 8x + 4 8r +4 . (b) . Y' – Y = (2x + xe2+ 22,21 & y'y = + +
To solve the given differential equations using the method of undetermined coefficients, we need to find a particular solution that satisfies the non-homogeneous equation. So, the general solution is given by: (a) y = y_h + y_p = Ce^(4x) + (-x - 4xe^(-2x) + 8x^2 - 1)e^(-2x) + 8x - 1, (b) y = y_h + y_p = Ce^x + (-x + 22.21e^x)
Let's solve each equation separately:
(a) y' - 4y = 16xe^(-2x) + 8x + 4
Step 1: Solve the associated homogeneous equation:
The homogeneous equation is y' - 4y = 0, which has the solution y_h = Ce^(4x), where C is a constant.
Step 2: Track down a specific non-homogeneous equation solution:
Since the non-homogeneous term contains terms like xe^(-2x) and x, we assume a particular solution of the form:
y_p = (A + Bx)e^(-2x) + Cx + D
Differentiating y_p, we have:
y'_p = (-2A + B - 2Bx)e^(-2x) + C
Substituting y_p and y'_p into the original equation, we get:
(-2A + B - 2Bx)e^(-2x) + C - 4((A + Bx)e^(-2x) + Cx + D) = 16xe^(-2x) + 8x + 4
Matching coefficients of like terms on both sides, we get:
-2A + B - 4A - 4D = 0 (coefficients of e^(-2x))
-2B - 4C = 16x (coefficients of xe^(-2x))
-2A + C = 8x (coefficients of x)
-4D = 4 (constant term)\
Solving these equations, we find A = -1, B = -4, C = 8, and D = -1.
Therefore, the particular solution is:
y_p = (-x - 4xe^(-2x) + 8x^2 - 1)e^(-2x) + 8x - 1
The general solution is given by:
y = y_h + y_p = Ce^(4x) + (-x - 4xe^(-2x) + 8x^2 - 1)e^(-2x) + 8x - 1
(b) y' - y = (2x + xe^2) + 22,21
Step 1: Solve the associated homogeneous equation:
The homogeneous equation is y' - y = 0, which has the solution y_h = Ce^x, where C is a constant.
Step 2: Track down a specific non-homogeneous equation solution:
Since the non-homogeneous term contains terms like 2x, xe^2, and 22.21, we assume a particular solution of the form:
y_p = Ax + B + Cx^2 + De^x
Differentiating y_p, we have:
y'_p = A + C + 2Cx + De^x
Substituting y_p and y'_p into the original equation, we get:
(A + C + 2Cx + De^x) - (Ax + B + Cx^2 + De^x) = (2x + xe^2) + 22.21
Matching coefficients of like terms on both sides, we get:
A - Ax = 2x + xe^2 (coefficients of x)
C - Cx^2 = 0 (coefficients of x^2)
C + D = 22.21 (constant term)
According to the first equation, A = -1.
From the second equation, we have C = 0.
Substituting A = -1 and C = 0 into the third equation, we get D = 22.21.
Therefore, the particular solution is:
y_p = -x + 22.21e^x
The general solution is given by:
y = y_h + y_p = Ce^x + (-x + 22.21e^x)
For more questions on: coefficients
https://brainly.com/question/30845099
#SPJ8
what is the length (in cm) of a pendulum that has a period of 0.537 s?
The length of the pendulum is approximately 24.99 cm.
The formula for the period of a pendulum is:
T = 2π√(L/g)
where T is the period in seconds, L is the length of the pendulum in meters, and g is the acceleration due to gravity (approximately 9.81 \(m/s^2\)).
To find the length L of the pendulum in centimeters, we can rearrange the formula as follows:
L = (T/2π\()^2\) * g
Substituting T = 0.537 s and g = 9.81 m/s^2 (which is equivalent to 981 cm/s^2), we get:
L = (0.537/(2π)\()^2\) * 981
L ≈ 24.99 cm
Therefore, the length of the pendulum is approximately 24.99 cm.
Learn more about period of a pendulum:
https://brainly.com/question/14759840
#SPJ4
Which Is The Simplified Rational Expression?
Answer:
1st choice
Step-by-step explanation:
(r² -4r + 5 - r² -2r + 8) / (r - 4)
= (-6r + 13) / (r - 4)